2020
DOI: 10.3390/cancers12041042
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG and 11C-Methionine PET/CT in Newly Diagnosed Multiple Myeloma Patients: Comparison of Volume-Based PET Biomarkers

Abstract: 11 C-methionine ( 11 C-MET) is a new positron emission tomography (PET) tracer for the assessment of disease activity in multiple myeloma (MM) patients, with preliminary data suggesting higher sensitivity and specificity than 18 F-fluorodeoxyglucose ( 18 F-FDG). However, the value of tumor burden biomarkers has yet to be investigated. Our goals were to corroborate the superiority of 11 C-MET for MM staging and to compare its suitability for the assessment of metabolic tumor burden biomarkers in comparison to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 29 publications
(60 reference statements)
0
30
0
1
Order By: Relevance
“…Thus, they demonstrated that MET uptake was correlated with bone marrow involvement, β2-microglobulin and free light chain levels, and appears to be a more accurate market of tumor burden compared to 18 FDG [43]. Another recent study confirmed the excellent sensitivity of MET for the assessment of MM tumor burden compared to 18 FDG [44]. Nevertheless, the prognostic value of this tracer need further investigation particularly in comparison with 18 FDG, which is currently the strongest marker in this pathology.…”
Section: Perspectivementioning
confidence: 93%
“…Thus, they demonstrated that MET uptake was correlated with bone marrow involvement, β2-microglobulin and free light chain levels, and appears to be a more accurate market of tumor burden compared to 18 FDG [43]. Another recent study confirmed the excellent sensitivity of MET for the assessment of MM tumor burden compared to 18 FDG [44]. Nevertheless, the prognostic value of this tracer need further investigation particularly in comparison with 18 FDG, which is currently the strongest marker in this pathology.…”
Section: Perspectivementioning
confidence: 93%
“…MET is able to reflect the synthetic protein turnover by malignant cells and its uptake is not influenced by non-disease related determinants of bone marrow tracer uptakes such as anemia or systemic inflammation. This feature results in a good sensitivity concerning FDG in describing the degree of bone infiltration in the staging phase [ 61 , 62 , 63 ], even when low monoclonal protein-producing myelomas such as IgD, IgE and non-secretory types are studied [ 64 ]. The higher adherence of MET uptake (compared with FDG uptake) to the proliferative activity of MM resulted also in a higher sensitivity in the detection of minimal residual disease in a young patient with an unusual extramedullary (vulvar) presentation of recurrent MM [ 65 ].…”
Section: Non-fdg Pet Tracers In the Post-treatment Setting Of Multmentioning
confidence: 99%
“…В 2020 г. M. Morales-Lozano и соавт. [13] представили результаты исследований 22 пациентов с впервые выявленной ММ, до начала лечения, которым выполняли ПЭТ как с 18F-ФДГ, так и с 11 C-Мет. Предварительные результаты показали преимущество 11 C-Мет в определении распространения опухолевого поражения в сравнении с 18F-ФДГ.…”
Section: множественная миеломаunclassified